ACADEMIC SUPERVISION MODEL THROUGH A COLLABORATIVE APPROACH BASED ON HEARING ABILITY, ABILITY TO RESPOND, SELF-EFFICACY, AND ALTRUISTIC ATTITUDE (M2EA) TO ALIYAH MADRASSA SUPERVISORS IN THE MINISTRY OF RELIGIOUS AFFAIRS OF MEDAN CITY - Tutik Sugesti (Proceeding International Seminar of Islamic Studies, 2022)
This research aims to develop a model of planning, implementation, evaluation, and follow-up of academic supervision through a collaborative approach based on hearing ability, ability to respond, self-efficacy, and altruistic attitude (M2EA) to the supervisor of madrasah aliyah in the ministry of the religion of Medan city. The subjects and objects of the study are supervisors, principals, and teachers at the Madrasah Aliyah Ministry of Religious Affairs of Medan City. Research is a form of research and development, where the approach is used through mixed methods with sequential explanatory techniques. Data analysis techniques use descriptive statistical techniques for quantitative data, while qualitative data analysis uses broad and in-depth use of field data. The study findings explain that the academic supervision model through hearing ability, ability to respond, self-efficacy attitude and altruistic attitude (M2EA) must be carried out through several stages, namely: first, planning stage, gathering supervisors, principals, and teachers in the form of scientific meetings, to provide information about collaborative-based academic supervision using M2EA; second, the pre-supervised meeting stage, listening supervisors. Keywords: Academic Supervision, Collaborative, Ability, Altruistic.